Price list for eyeglasses, spectacles and lenses (1929)
1929 1929 1920s 1 page NATIONAL OPHTHALMIC TREATMENT BOARD. PRICE LIST. The following are the prices of all frames supplied by the National Ophthalmic Treatment Board at their centres. GRADE "A" SERIES Best Quality White Metal Rimmed Spectacles ; Best Quality White Metal Rimmed Eyeglasses ; Best Quality White Metal Rimless Eyeglasses ; Glazed with any lenses ordered on prescription (with the exception of Crooke's Glass, Tinted Glass, Prisms or Bifocals, the extra cost of which are shown below) complete with case ... 7/6 GRADE "B" SERIES. Best Quality 1/10th 10ct. Gold Filled Rimmed Spectacles ; Best Quality 1/10th 10ct. Gold Filled Rimmed Eyeglasses ; Best Quality 1/10th 10ct. Gold Filled Rimless Eyeglasses ; Lenses as specified above, with metal case ... ... 15/- GRADE "C" SERIES. Best Quality 1/10th 10ct. Gold Filled Rimmed Spectacles, with Zylo Covered Rims ; Imitation Shell, straight or bent over sides, Rimmed Spectacles ; Imitation Shell, with Gold Filled Curled Sides ; Two patterns 1/10th 10ct. Gold Filled Rimmed Eyeglasses, with Zylo Covered Rims ; 1/10th 10ct. Gold Filled Rimless Spectacles ; Lenses as specified above, with metal snap case ... ... 22/6 The prices of special lenses are as follows:— Segment Bifocal Lenses 10/- Tinted Plano Lenses 2/- Tinted Lenses 4/- Crookes' Plano Lenses 4/- Crookes' Lenses 8/- Prisms ½-4 Dioptres 5/- Prisms 4½-6 Dioptres 6/- 292/841.4/1/59